EXAMINING THE POTENTIAL OF ENTOMOPATHOGENIC FUNGI AS AN ALTERNATIVE TO CHEMICAL INSECTICIDES FOR CULEX QUINQUEFASCIATUS CONTROL - Suleiman, sani (International Journal of Allied Sciences (IJAS), 2023)
Mosquito species that transmit parasitic diseases are typically controlled using chemical insecticides, which can harm the environment and public health. This study assesses the potential of the entomopathogenic fungus Metarhizium anisopliae as an eco-friendly alternative for controlling Culex quinquefasciatus larvae in the lab. After treating fourth instar larvae with various concentrations of the fungus, mortality rates were monitored over 120 hours. The results indicate that Metarhizium anisopliae could be a viable bio-control agent for Culex quinquefasciatus and merits further investigation. The experiment was allowed to run for a period of 120 hours. Mortality was recorded at an interval of 24 hours. Probit analysis was used to determine LC50, LC90, LC95 and LC99. For all the selected concentration, highest mortality of 42(70,0%), 48(80.0%), 51(85.0%) and 57(95.0%) were recorded after 120 hour. 1.79 x 103, 3.96 x 104, 4.97 x 105, 7.58 x 108 conidia/ml were the LC50, LC90, LC95 and LC99 recorded respectively. Metarhizium anisopliae has the potential to be used as bio control agent for Culex quinquefasciatus and is suitable candidate for further research